Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2478/johh-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of water use of Pinus tabulaeformis Carr. in Loess Plateau of Northwest China

Abstract: Tree transpiration plays a determining role in the water balance of forest stands and in seepage water yields from forested catchments, especially in arid and semiarid regions where climatic conditions are dry with severe water shortage, forestry development is limited by water availability. To clarify the response of water use to climatic conditions, sap flow was monitored by heat pulse velocity method from May to September, 2014, in a 40–year–old Pinus tabulaeformis Carr. plantation forest stands in the semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Sap ow P was initially analyzed with atmospheric conditions as a random effect, but adjustments were made due to the high variance between sunny and cloudy conditions. Sap ow P collected during cloudy conditions were increased by 100% based on ndings from previous studies (Xia et al 2008;Jian et al 2019) that reported similar increases during overcast conditions for translocated P. Differences between carryover treatments from Year 0 to Year 1 were analyzed using a two-way ANOVA with P fertilization treatment and treatment year as xed effects. Carryover treatments were separately analyzed within each treatment year and site using one-way ANOVA.…”
Section: Statisticsmentioning
confidence: 99%
“…Sap ow P was initially analyzed with atmospheric conditions as a random effect, but adjustments were made due to the high variance between sunny and cloudy conditions. Sap ow P collected during cloudy conditions were increased by 100% based on ndings from previous studies (Xia et al 2008;Jian et al 2019) that reported similar increases during overcast conditions for translocated P. Differences between carryover treatments from Year 0 to Year 1 were analyzed using a two-way ANOVA with P fertilization treatment and treatment year as xed effects. Carryover treatments were separately analyzed within each treatment year and site using one-way ANOVA.…”
Section: Statisticsmentioning
confidence: 99%